The effect of environmental awareness as a moderation on determinants of green product purchase intention - A.S. Rama; . Yasri; P. Susanto (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: This study aims to determine the effect of green brand positioning and knowledge and attitudes toward green brands on green product purchase intention moderated by environmental awareness. Collected data were from 230 Generation Y respondents in West Sumatra, Indonesia, who intended to purchase a low-cost green car. The achievement of this research is the implementation of environmental management policies in West Sumatra by increasing Generation Y awareness to buy green products to maintain the carrying capacity of the environment and encourage changes in environmentally conscious behavior.METHODS: This study used a survey approach with a questionnaire. The population in this study is Generation Y in West Sumatra, who intend to buy low-cost green cars. This study used a nonprobability approach in the sample selection. A purposive sampling technique was applied, and data were analyzed using a structural equation model – the partial least squares method.FINDINGS: There are five crucial findings in this study. First, green brand positioning has a significant effect on attitudes toward green brands, green product purchase intention, and green brand knowledge, which are 0.192, 0.151, and 0.680, respectively. Second, green brand knowledge has a significant effect on attitudes toward green brands and green product purchase intention, which are 0.271 and 0.229, respectively. Third, attitudes toward green brands have a significant effect on green product purchase intention of 0.067. Fourth, attitudes toward green brands mediate green brand positioning and knowledge on green product purchase intention by 0.218 and 0.057, respectively. Fifth, environmental awareness has a moderating effect between attitudes toward green brands and green product purchase intention at 0.161 but does not have a moderating effect between green brand positioning and green product purchase intention.CONCLUSIONS: The findings of this study are for green marketers to supply high access levels to green product demand because consumers are increasingly aware of environmental preservation, and marketers must emphasize quality, price, and advertising to increase demand for green products. Moreover, the respondents were only taken from West Sumatra Province, so the study results cannot represent the entire country (Indonesia). Therefore, further research should attempt to expand the sample size to include more provinces in Indonesia. Finally, this study used a cross-sectional research design, which gathered data simultaneously.